KEBERLANJUTAN PROGRAM POS PELAYANAN TERPADU PADA ERA PENERAPAN DANA DESA DI KABUPATEN BANJARNEGARA - Sri Budi Utami; Yodi Mahendradhata; Ari Probandari (Berita Kedokteran Masyarakat (BKM), 2020)
Purpose: This study aims to analyze good practices for the sustainability of  Village Fund supported posyandus in Banjarnegara District.Methods: This study used a qualitative approach with a descriptive case study design. The study used purposive sampling with 23 informants. We used in-depth interviews for data collection.Result: Posyandu sustainabilityis supported by the stability of funding sourced from the Village Fund as the main financing strategy. Six Domains of Posyandu Sustainability for political support, funding stability, partnerships, organizational capacity, evaluation, and communication that still need to be strengthened are the organizational capacity of Posyandu. It is necessary to refer to Permendagri No. 18 of 2018. Posyandu sustainability in rural areas is better than in urban areas.Conclusion: It is necessary to strengthen the domain of posyandu organizational stability, with the strengthening of Posyandu institutions that will impact the support policies of villages / sub-districts to Posyandu.